2019
DOI: 10.1136/bmjopen-2019-033421
|View full text |Cite
|
Sign up to set email alerts
|

Journal editors’ perspectives on the roles and tasks of peer reviewers in biomedical journals: a qualitative study

Abstract: ObjectivePeer reviewers of biomedical journals are expected to perform a large number of roles and tasks, some of which are seemingly contradictory or demonstrate incongruities between the respective positions of peer reviewers and journal editors. Our aim was to explore the perspectives, expectations and understanding of the roles and tasks of peer reviewers of journal editors from general and specialty biomedical journals.DesignQualitative study.SettingWorldwide.Participants56 journal editors from biomedical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 31 publications
1
49
1
3
Order By: Relevance
“…Besides this, our study confirmed the findings of previous studies. This included assessing the contributions of a manuscript (Ware, 2008a(Ware, , 2008b, quality control (Mulligan et al, 2013;VanTassell et al, 1992;Ware, 2008a), improvement of a manuscript (Mulligan et al, 2013;Nicholas et al, 2015;Rowlands & Nicholas, 2006;VanTassell et al, 1992;Ware, 2008b), assessing the suitability of a manuscript for a particular journal (Mulligan et al, 2013;VanTassell et al, 1992), providing a decision-making tool for editors (Glonti et al, 2019), and providing of a seal of accreditation or approval for published contents (Nicholas et al, 2015;Ware, 2008a). Another key finding was that stakeholders with different roles and tasks in the review process differed in their understanding of and the value they attached to functions of peer review.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, our study confirmed the findings of previous studies. This included assessing the contributions of a manuscript (Ware, 2008a(Ware, , 2008b, quality control (Mulligan et al, 2013;VanTassell et al, 1992;Ware, 2008a), improvement of a manuscript (Mulligan et al, 2013;Nicholas et al, 2015;Rowlands & Nicholas, 2006;VanTassell et al, 1992;Ware, 2008b), assessing the suitability of a manuscript for a particular journal (Mulligan et al, 2013;VanTassell et al, 1992), providing a decision-making tool for editors (Glonti et al, 2019), and providing of a seal of accreditation or approval for published contents (Nicholas et al, 2015;Ware, 2008a). Another key finding was that stakeholders with different roles and tasks in the review process differed in their understanding of and the value they attached to functions of peer review.…”
Section: Discussionmentioning
confidence: 99%
“…This attitude is in line with findings that highlighted journal editors’ apparent lack of appreciation for formal peer reviewer training. 7 In both cases, the justification was the same: peer reviewers should know how to review a manuscript without needing guidelines and training. Such an approach to the communication of roles and tasks is likely to be an obstacle to mutual understanding and may ultimately impact the quality of reports received.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the study design and methodology is available elsewhere 6 as well as in a related study using this dataset. 7 A brief description of the key methodological components follows below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publishers and editors usually are not represented in these surveys and junior scholars are often under-represented. Qualitative analyses of stakeholder perceptions are another strand of research (Glonti et al, 2019;Harley et al, 2010;Severin and Chataway, 2020;University of Tennessee and CIBER Research Ltd, 2013). This research is not focused on reviewing burden, but indicates that stakeholders generally differ in their perceptions of challenges in peer review and respective solutions.…”
Section: Introductionmentioning
confidence: 99%